2017
DOI: 10.3389/fcimb.2017.00300
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes Phospholipase A2 Induces the Expression of Adhesion Molecules on Human Umbilical Vein Endothelial Cells and Aorta of Mice

Abstract: The Streptococcus pyogenes phospholipase A 2 (SlaA) gene is highly conserved in the M3 serotype of group A S. pyogenes, which often involves hypervirulent clones. However, the role of SlaA in S. pyogenes pathogenesis is unclear. Herein, we report that SlaA induces the expression of intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) via the arachidonic acid signaling cascade. Notably, recombinant SlaA induced ICAM1 and VCAM1 expression in human umbilical vein endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Icam1 and Serpina10 may indicate infection in the liver, while Orm2 may indicate progression to the heart. Previous reports have shown that Icam1 expression is induced by GAS's SlaA, increasing the adhesion of human monocytic leukemia cells (Oda et al, 2017). Icam1 deletion mutants have also displayed increased bacterial burden in Mycobacterium infection, further evidence of a role for Icam1 during bacterial infection (de Paula et al, 2017).…”
Section: Blood Markers Of Systemic Bacterial Infectionmentioning
confidence: 92%
“…Icam1 and Serpina10 may indicate infection in the liver, while Orm2 may indicate progression to the heart. Previous reports have shown that Icam1 expression is induced by GAS's SlaA, increasing the adhesion of human monocytic leukemia cells (Oda et al, 2017). Icam1 deletion mutants have also displayed increased bacterial burden in Mycobacterium infection, further evidence of a role for Icam1 during bacterial infection (de Paula et al, 2017).…”
Section: Blood Markers Of Systemic Bacterial Infectionmentioning
confidence: 92%
“…ExoU liberates AA from eukaryotic cell membrane, an activity required for its toxicity (Rabin & Hauser, ; Saliba et al, ). Other bacterial phospholipases implicated in host interaction include Streptococcus pyogenes phospholipase A 2 SlaA (Oda et al, ) and the ExoU homologue VipD in Legionella pneumophila (Gaspar & Machner, ; Ku et al, ).…”
Section: Microbial Oxylipins: Enzymes and Productsmentioning
confidence: 99%
“…The L. pneumophila homologue of ExoU, VipD disrupts endosomal membrane lipids and facilitates L. pneumophila escape from endosomal fusion in the Cos‐1 cells (Gaspar & Machner, ). S. pyogenes phospholipase A 2 SlaA increases monocyte adhesion to endothelial cells in vitro (Oda et al, ).…”
Section: Microbial Oxylipins: Effect On Inflammation and Virulencementioning
confidence: 99%
“…Furthermore, pneumococcal phospholipase A2 (PLA2), which is a secreted bacterial enzyme that also modulates inflammation [ 63 ], is a clinical predictor for PM [ 64 ]. PLA2 production is associated with upregulation of adhesion molecules in host vascular endothelial cells [ 65 ].…”
Section: The Bbb In Acute Pmmentioning
confidence: 99%